(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
The contemporary landscape of education in technical and engineering disciplines is marked by an increasing reliance on digital programs to facilitate a deeper and more comprehensive understanding of theoretical and practical aspects of the subject matter. In structural mechanics and material sciences, the concepts of tensile and compressive deformation are foundational topics that require not only conceptual clarity but also a heightened ability to analyze and visualize stress-strain behavior under different loading conditions. The use of digital programs in teaching these concepts enhances pedagogical effectiveness and student engagement by offering dynamic, interactive, and precise methods for illustration and analysis.